ответ:1-oе фото
1)x²-2x-35 2)3x²+16x+5 3)x²-13x+40
x²-2x-35=0 3x²+16x+5=0 x²-13x+40=0
D=4+4*35=144 D=256-4*3*5=196 D=169-4*40=9
x1=(2+12):2=7 x1=(-16+14):6=5 x1=(13+3):2=8
x2=(2-12):2=-5 x2=(-16-14):6=0,3333333 x2=(13-3):2=5
4)6x²+x-1
6x²+x-1=0
D=1+4*6*1=25
x1=(-1+5):12=0,3333333
x2=(-1-5):12=-0,5
a) -x²+9x-8 = -x²+x+8x-8 = (-x²+x)+(8x-8) = -x(x-1) + 8(x-1) =
= (x-1)(-x+8) =(x-1)(8-x)
б)![\frac{1}{3}x^{2}+x-6=\frac{1}{9}(3x^{2}+9x-54)=\frac{1}{9}(3x^{2}+18x-9x-54)=](/tpl/images/0930/2558/2a964.png)